2019
DOI: 10.3791/60294
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Intracellular ATP in Organotypic Tissue Slices of the Mouse Brain using the FRET-based Sensor ATeam1.03<sup>YEMK</sup>

Abstract: Neuronal activity in the central nervous system (CNS) evokes a high demand on cellular energy provided by the breakdown of adenosine triphosphate (ATP). A large share of ATP is needed to re-install ion gradients across plasma membranes degraded by electrical signaling of neurons. There is evidence that astrocytes-while not generating fast electrical signals themselves-undergo increased production of ATP in response to neuronal activity and support active neurons by providing energy metabolites to them. The rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Still, the swelling of neuronal cell bodies was less pronounced than that of astrocytes observed before (N = 5; compare Figures 1B,D). However, when opening the glial scar covering organotypic slices as recently described (Lerchundi et al, 2019b), neurons rounded up more strongly in response to perfusion with β-escin, suggesting a better permeabilization of the cells (N = 5; Figure 3).…”
Section: Atp Sensitivity Of Ateam103 Yemk Expressed In Neuronssupporting
confidence: 53%
See 3 more Smart Citations
“…Still, the swelling of neuronal cell bodies was less pronounced than that of astrocytes observed before (N = 5; compare Figures 1B,D). However, when opening the glial scar covering organotypic slices as recently described (Lerchundi et al, 2019b), neurons rounded up more strongly in response to perfusion with β-escin, suggesting a better permeabilization of the cells (N = 5; Figure 3).…”
Section: Atp Sensitivity Of Ateam103 Yemk Expressed In Neuronssupporting
confidence: 53%
“…Activityrelated increases in extracellular K + , which result in a depolarization of astrocytes, activate the electrogenic sodium-bicarbonate-cotransporter NBCe1, inducing a cytosolic alkalization and, as consequence, a stimulation of glycolysis (Bittner et al, 2011;Ruminot et al, 2011;Choi et al, 2012). In line with this, an exposure of astrocytes to a brief period of elevated extracellular K + produces a reversible increase in their cellular ATP level (Fernández-Moncada et al, 2018;Lerchundi et al, 2019b).…”
Section: Differential Metabolic Response Of Neurons and Astrocytes Tomentioning
confidence: 87%
See 2 more Smart Citations
“…2G). Notably the ATeam ratio does not change under control conditions within this time frame (Lerchundi et al 2019a), indicating that the slow decline observed in the present study was indeed related to the ongoing activity induced by the dis-inhibition.…”
Section: Network [Na + ] Oscillations Induce a Decrease In Neuronal [mentioning
confidence: 99%